Role of fatty acids in autoxidation of deproteinised natural rubber - Arnold, A. R. (2018)
The effects of stearic, oleic and linoleic acids and their methyl esters on the autoxidation of deproteinised natural rubber (DPNR) have been investigated. The carboxyl group of the free acids was found to be of primary importance in increasing the rate of oxidation and enhancing chain scission. Oleic and linoleic acids exhibited synergistic pro-oxidant activity as a result of their co-oxidation. Chain breaking antioxidants such as butylated hydroxy toluene (BHT) helped protect polyisoprene from fatty acid promoted autoxidation.